Papel das citocinas na proteinúria da erliquiose aguda e subclínica em cães - Pennacchi, Caio Santos (2023)
Canine ehrlichiosis is an infectious disease caused by the bacteria Ehrlichia spp., described worldwide. Dogs with ehrlichiosis are more predisposed to develop acute kidney injury and consequently chronic kidney disease. Variations in the inflammatory response caused by the host result in different phases, being acute, subclinical and chronic. In each of them, the development of multisystemic comorbidities is possible, with glomerulonephritis being commonly observed. Thus, the present study aimed to evaluate the pathophysiology of proteinuria and acute kidney injury in canine ehrlichiosis, analyzing the profile of inflammatory cytokines and correlating them with renal parameters in canine patients spontaneously infected with E. canis in the acute and subclinical phases. Through a better understanding of the pathophysiology of the disease, it is possible to promote advances in treatments in veterinary and human medicine. To carry out the study, 58 dogs of varying breed, age, sex and weight were recruited and allocated into three distinct groups. After clinical and laboratory evaluation, 18 animals were included in the group of healthy dogs (Control Group-CG). Dogs with a strictly positive molecular diagnosis for E. canis, with the presence of clinical manifestations were included in the group of animals with acute disease (ADG; n=24), and those with a strictly positive molecular and serological diagnosis for E. canis, however, without clinical signs and manifestations, they were considered to have subclinical disease (SCG; n=16). The cytokines TNFα, IL-4, IL-6, INF-ᵧ and IL-10 were evaluated. All cytokines showed statistical differences (p<0.0001) in relation to the aforementioned groups. TNFα, IL-4, IL-6 and INF-ᵧ showed an increased pattern in GDA and GSC. There was a positive correlation between TNFα, INF-ᵧ and IL-10 and proteinuria in the GDA, as well as a negative correlation between IL-10 and proteinuria in the GSC. Thus, it is concluded that TNFα and INF-ᵧ are related to the acute inflammation of the disease, while IL-10 seems to attenuate the clinical manifestations, but not proteinuria. In both phases, such cytokines have the potential to cause proteinuria, and consequently lead to kidney damage in infected dogs.